Assessing the Impact of Remittances on Economic Growth and Household Welfare in Haiti - Jean-Baptiste Innocent Nyangoma, Jean-Baptiste Innocent Nyangoma; Carlos Eduardo Martínez; Elena Petrova (Yayasan Amerta Insan Unggul, 2025)
This study examines the impact of international remittances on economic growth and household welfare in Haiti, a remittance-dependent economy where such inflows represent over 20% of GDP. Using annual time-series data from 2000 to 2023 obtained from the World Bank, IMF, and UNDP databases, the study applies the Autoregressive Distributed Lag (ARDL) bounds testing approach to assess both short-run and long-run dynamics among remittances, GDP growth, and household consumption. The empirical results indicate that remittances exert a statistically significant and positive effect on economic growth in the long run, primarily through increased household income, consumption expenditure, and investment in education and health. However, in the short run, remittance inflows exhibit a neutral effect on growth due to high import dependency and weak financial intermediation. Furthermore, the study finds that remittances contribute to household welfare improvement by reducing poverty incidence and income inequality, although their developmental potential is constrained by Haiti’s structural vulnerabilities and limited institutional capacity. The findings suggest that policies promoting financial inclusion, productive investment of remittances, and diaspora engagement could enhance the developmental role of remittances. This research provides new insights into the macroeconomic and social implications of remittance inflows in small developing economies and offers evidence-based recommendations for achieving inclusive and sustainable growth in Haiti.